Risk Preferences Are Not Time Preferences - Andreoni, James; Sprenger, Charles (American Economic Review, 2012)
Risk and time are intertwined. The present is known while the future is inherently risky. This is problematic when studying time preferences since uncontrolled risk can generate apparently present-biased behavior. We systematically manipulate risk in an intertemporal choice experiment. Discounted expected utility performs well with risk, but when certainty is added common ratio predictions fail sharply. The data cannot be explained by prospect theory, hyperbolic discounting, or preferences for resolution of uncertainty, but seem consistent with a direct preference for certainty. The data suggest strongly a difference between risk and time preferences. (JEL C91 D81 D91)